ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI CABAI RAWIT - Yohana Feldi Banung; Nyoman Yudiarini; Putu Fajar Kartika Lestari; Ida Ayu Made Dwi Susanti (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This research is intended to determine the income of Cayenne pepper farming and to analyze the factors that influence the production of cayenne pepper in Sukawati village, Sukawati District, Gianyar Regency. The method used was primary data and secondary data, and the data sources used were quantitative and qualitative analysis. The Analytical method used is income analysis and Cobb douglas function analysis. The number of samples in this study were 45 farmers consisting of 43 men and 2 women. From the results of the discussion , the productivity of cayenne pepper in sukawati village has an average of 391.11 kg 27.7 are or 1.411.39 kg per hectare (ha) this productivity is relatively low, this is because cayenne pepper nationally reaches 3-4 tons per hectare per season of cayenne pepper production. The results of the analysis of variance from the regression of the cayenne pepper production function show that (x1-x7) together have a very significant effect on the production of cayenne pepper (Y), which is indicated by the F value equal to 21.718 which is very significant ( p = 0.000). The results of the study found that the income earned in cayenne pepper farming in Sukawati village per planting season with an average land area of 27.7 acres reached Rp. 4.315.511 or Rp.15.579.462 per hectare per growing season. Significanttly there are four production factors that affect the production of cayenne pepper, namely the production factor of land area , number of seeds, organic fertilizer, and labor used.